Exploring Social Dynamics in Homestay: A study of Bethanchowk Village Community Homestay - Rawal, Sunil (Patan Prospective Journal, 2023)
This article explores the rich realm of home stays in Bethanchowk, revealing a complex web of cultural exchange, identity formation that is transformative, cooperative decision-making, and the significant impact of the local context. Host narratives shed light on the distinctive dynamics that distinguish home stays from other types of lodging. The process of cultural adaptation is gradual; visitors actively participate in local celebrations and customs, becoming essential strands in the rich tapestry of Bethanchowk culture. This mutual process enhances the travel experience for visitors while giving hosts priceless insights into various cultural viewpoints. Visitors who participate in a home stay experience leave with a small piece of the local identity, emphasizing transformative identity formation. By sharing their cultural heritage and encouraging positive metamorphoses, hosts contribute to influencing the perspectives of their guests. Established power structures in commercialized lodgings are challenged by the inclusive atmosphere, which values everyone and is characterized by group decision-making and a lack of hierarchy. This reciprocal experience is advantageous to guests as well as hosts. With a focus on the local environment, Bethanchowk's Village Community home stays provide visitors with a distinctive cultural experience through festivals, customs, and friendliness. Through cultural workshops and partnerships with local artisans, they work to continuously improve the home stay, making it flexible enough to adjust to guests' changing tastes and preserve its distinct ambience outside of the building. Home stay narratives are sociologically innovative spaces that transcend traditional hospitality models, fostering social interactions, cultural exchange, and identity co-creation. These findings highlight evolving consumer behavior in the hospitality sector and guide home stays towards a future where cultural exchange and enriched experiences remain at the forefront of innovation, guiding them towards a more fulfilling and enriching experience.